Efficacy of combined immunotherapy with Propes and Inflamafertin in selective deficiency of NK and NKT cells in children with autism spectrum disorders associated with genetic deficiency of the folate cycle - Dmitry Maltsev; Volodymyr Stefanyshyn (Romanian Journal of Neurology, 2021)
Objectives. The results of previous small clinical trials indicate the potential benefit of combination immunotherapy with Propes and Inflamafertin to compensate for NK and NKT cell deficiency due to genetic deficiency of the folate cycle in children with autism spectrum disorders. The purpose of the research was to study the effectiveness of combined immunotherapy with Propes and Inflamafertin in NK and NKT cell deficiency in children with autism spectrum disorders associated with genetic deficiency of the folate cycle. Material and methods. This single-center, prospective, controlled, nonrandomized clinical trial included 96 children aged 2 to 10 years with autism spectrum disorders associated with a genetic folate deficiency (study group, SG). Children of SG received Propes at a dose of 2 ml IM every other day for 3 consecutive months (45 injections), and Inflamafertin at a dose of 2 ml IM every other day for 3 months in a row, alternating with Propes (45 injections). The control group (CG) consisted of 32 children of similar age and gender distribution who suffered from autism spectrum disorders associated with genetic deficiency of the folate cycle, but who did not receive immunotherapy. Outcomes. The number of NK cells reached the lower limit of normal in 39 out of 53 patients (74% of cases), with the resulting deficiency of these lymphocytes, and the average number of NK cells in the blood in SG almost doubling during the 3-month course of immunotherapy (р ˂ 0.05; Z ˂ Z0.05). However, it returned to almost initial level in the 2 months following the discontinuation of immunotherapeutic agents (р˃0.05; Z˃Z0.05). The number of NKT cells was normalized in 78 out of 87 patients (89% of cases) with an initial deficiency of these cells, and the average number of NKT cells in the blood in the DG increased during the course of immunotherapy by half (р ˂ 0.05; Z ˂ Z0.05) and continued to grow for the next 2 months after the discontinuation of immunotropic drugs (р ˂ 0.05; Z ˂ Z0.05). There was a link between immunotherapy and normalization of NK - (χ2 = 18.016; OR = 13.929; 95%CI = 3.498-55.468) and NKT-cells (χ2 = 60.65; OR = 46.800; 95%CI = 14.415-151.937) in the blood with a strong association between these processes (criterion φ = 0.504 and 0.715 respectively; С = 0.450 and 0.581 respectively). Conclusions. Combination immunotherapy with Propes and Inflamafertin is an effective strategy for the treatment of immunodeficiency caused by genetic deficiency of the folate cycle in children with autism spectrum disorders.